THE EFFECT OF CAPITAL STRUCTURE ON PROFITABILITY IN ANIMAL FEED SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Husnul Khatima; Muh. Ikhwan Maulana Haeruddin; Anwar; Romansyah Sahabuddin; Burhanuddin (Journal Management & Economics Review (JUMPER), 2023)
This study aims to determine the effect of capital structure on profitability in animal feed sub-sector companies listed on the Indonesian stock exchange. This type of research is Quantitative Descriptive. This study uses the independent variable capital structure, which is proxied by the ratio of debt to equity or Debt To Equity Ratio (DER). The dependent variable is profitability. Profitability is calculated using the Return On Equity (ROE) ratio. The data used is secondary data derived from the financial statements of animal feed sub-sector companies listed on the Indonesia Stock Exchange in 2014-2021. Samples were taken using the saturated sample method, in order to obtain a sample that met the requirements of 4 companies. The data analysis technique used is simple linear regression with hypothesis testing using the t statistical test, besides that a classic assumption test is also carried out which includes linearity tests, normality tests, and autocorrelation tests. The results of the analysis show that capital structure (DER) has a negative and significant effect on profitability (ROE) in animal feed sub-sector companies listed on the Indonesia Stock Exchange, this negative direction means that the greater the DER value owned by a company identified with total debt, the lower the profitability (ROE) value obtained by the company. The predictive ability of the DER variable on ROE is 23.8% as shown by R Square of 23.8%, while the remaining 76.2% is influenced by other factors not examined.